1995
DOI: 10.1111/j.1365-2125.1995.tb04424.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fasting on total serum bilirubin concentrations.

Abstract: Thirty-seven healthy volunteers, 19 of whom had consistently elevated total serum bilirubin (TSB) concentrations, took part in an open, randomised cross-over study to determine the effect of fasting on TSB concentrations. The study comprised of two treatments. During one treatment period volunteers ate a standard supper but fasted for 24 h thereafter. During the other treatment period volunteers ate a standard supper, snacks, breakfast and lunch. TSB concentrations were measured at regular intervals. In both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 6 publications
3
13
0
Order By: Relevance
“…We have shown that bilirubin has a hormonal function by binding directly to the fat-burning nuclear receptor PPARα inducing transcriptional activity and gene regulation [18][19][20]. PPARα is induced by fasting [21], which is also when bilirubin is the highest [11][12][13][14]. There may be a bilirubin-induced endocrine function during fasting, which has been shown for PPARα-mediated induction of fibroblast growth factor 21 (FGF21) [22].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have shown that bilirubin has a hormonal function by binding directly to the fat-burning nuclear receptor PPARα inducing transcriptional activity and gene regulation [18][19][20]. PPARα is induced by fasting [21], which is also when bilirubin is the highest [11][12][13][14]. There may be a bilirubin-induced endocrine function during fasting, which has been shown for PPARα-mediated induction of fibroblast growth factor 21 (FGF21) [22].…”
Section: Introductionmentioning
confidence: 94%
“…The enzyme that produces bilirubin, BVRA [6,7], is also reduced in obese humans compared to lean matched controls [8]. Studies indicate that bilirubin levels might increase with exercise [9,10] and fasting [11][12][13][14], implying a possible role for metabolic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows that the nutritional interventions used in this study induce rapid biochemical changes and these results point to good protocol adherence. Fasting decreases postabsorptive glucose and increases ketone bodies and total bilirubin levels as expected [20,21], but interestingly also GGT was significantly increased which refers to the process of hepatic steatosis [14]. The three-day high-fat diet increased post-absorptive glucose, GGT and alkaline phosphatase levels.…”
Section: Discussionmentioning
confidence: 53%
“…Although there has been some reporting of this association in the literature in the past,1 this is by far the largest study of this type reported to date.…”
Section: Discussionmentioning
confidence: 84%